A novel approach to neurologic function sparing surgical management of vagal schwannomas: Continuous intraoperative nerve monitoring of the laryngeal adductor reflex. Issue 9 (6th May 2019) - Sandler, Mykayla L.; Sims, John R.; Sinclair, Catherine; Ho, Rebecca; Yue, Lauren E.; Téllez, Maria J.; Ulkatan, Sedat; Khorsandi, Azita S.; Brandwein‐Weber, Margaret; Urken, Mark L.
Abstract: Background: Vagal schwannomas are rare, benign tumors of the head and neck. Nerve damage during surgical resection is associated with significant morbidity. A new technique of continuous intraoperative nerve monitoring (IONM) that allows for real‐time intraoperative feedback has recently been used for thyroid and cervical spine surgeries but has not previously been used in vagal schwannoma surgery. Methods: Case series of three patients who underwent vagal schwannoma excision utilizing this novel IONM technique. The recurrent laryngeal and vagus nerves were monitored via the laryngeal adductor reflex (LAR) using an electromyographic endotracheal tube. Results: Three patients with suspected vagal schwannomas were treated surgically using the intracapsular enucleation approach with a combination of intermittent IONM and continuous IONM of the LAR. Conclusion: This combination of continuous and intermittent IONM can be used to preserve vagal laryngeal innervation and function and may represent the future standard of care for vagal schwannoma excision.